The Ethics of Software Engineering Should be an Ethics for the Client. (Communications of the ACM, 2012)
The author argues that software engineering should be viewed as a form of communication with consumers subject to ethical considerations. According to the author, technological advances on a global scale require adjusted perspectives from software engineers and developers. Topics include parallel computing, the software engineering code of ethics, and character development through patience and honesty.